Home is home : a new approach to affordable housing in fietas - Sadie, Francis (My University, 2017)
In Johannesburg, affordable housing exists in two prevailing conditions. Either, it exists, in abundance as a housing-forownership model, in the form of low-density, free-standing RDP houses in low-income housing developments located on the periphery of the city, or it exists in scarce supply as rentable units in high-rise apartment blocks in the inner city. The growing number of people living in inadequate conditions in informal settlements, back yard shacks and inner city ‘bad’ buildings shows that the current models of affordable housing are inappropriate, and, points to the need for a new approach to meet the city’s affordable housing backlog. This research document proposes a new model of affordable housing in Fietas, a suburb within the inner city of Johannesburg, one of Gauteng and the country’s economic centres. The document is split into two parts: a theoretical section and a contextual section. The theoretical section discusses the importance of embodying a design approach, and therefore the role of the architect, in the implementation of affordable housing to improve the quality of life for users - a vulnerable section of society. The discussion takes place through the examination of selected affordable housing precedents that have been built at different times in different parts of the world, with a focus on Johannesburg. Underlying this discussion is the notion that an improved quality of life is what makes affordable housing affordable. The second part of this research document highlights the current affordable housing challenge in Johannesburg and proposes a possible solution to the challenge that is neither a high-rise inner-city apartment block, nor a low-density RDP house, but rather a solution that exists in between these two scales. Fietas is selected as an ideal site for this affordable housing solution because of its middle density scale and close proximity to the inner city of Johannesburg with the resultant opportunities that come with this location. Through the analysis of the area and the surrounding context a new model and alternative approach to affordable housing is developed. The research showed that no single solution would be able to solve the entire affordable housing challenge. However, this new model of affordable housing in Fietas offer a different approach to the challenge, one that offers more variety than Johannesburg’s two current models of affordable housing. Furthermore, this solution attempts to engage with the discourse of affordability in housing and the current challenges that exist around this often controversial topic of conversation.